Evaluation of the Enzymatic Production and Prebiotic Activity of Galactomannan Oligosaccharides Derived from Gleditsia microphylla - Hanghong Wang; Chenhuan Lai; Yuheng Tao; Mengyi Zhou; Ruilin Tang; Qiang Yong (Fermentation, 2023)
Oligosaccharides have received considerable attention as prebiotics because they exhibit potential health benefits related to their ability to modulate intestinal bacterial composition. This study evaluated the effects of galactomannan oligosaccharides (GMOS) derived from Gleditsia microphylla as a prebiotic on human intestinal bacteria. The β-mannanase used for the enzymatic hydrolysis of GMOS was produced by Trichoderma reesei Rut C-30. The enzymatic hydrolysis of GMOS was found to occur under optimal conditions at 50 °C, pH 5, 20 U/g-GM, and 20 g/L, and resulted in a yield of 70.78% ± 1.34%. The purity of GMOS after purification was 81.50%. Upon performing in vitro human fecal fermentation using GMOS as a carbon source, it was observed that GMOS effectively promoted the proliferation of intestinal bacteria, and the utilization efficiency of GMOS by intestinal bacteria was found to be at 98.40%. In addition, GMOS were found to have a stabilizing effect on intestinal pH. Additionally, 16S rRNA sequencing of GMOS revealed that GMOS significantly affected the diversity of gut microbiota. Specifically, GMOS exhibited a significant inhibitory effect on Fusobacteria at the phyla and genus level, and demonstrated a significant inhibitory effect on Fusobacterium. Moreover, the results for the prediction of metabolic function analysis showed that GMOS had a significant effect on the level two metabolism of carbohydrates, cofactors, and vitamins. Furthermore, during level three metabolism, the lipoic acid metabolism was significantly affected by GMOS. These results provide a theoretical basis for the potential use of galactomannan oligosaccharides from Gleditsia microphylla as prebiotics for regulating human intestinal bacteria.